2010
DOI: 10.1007/jhep07(2010)050
|View full text |Cite
|
Sign up to set email alerts
|

Non-equilibrium condensation process in a holographic superconductor

Abstract: We study the non-equilibrium condensation process in a holographic superconductor. When the temperature T is smaller than a critical temperature T c , there are two black hole solutions, the Reissner-Nordström-AdS black hole and a black hole with a scalar hair. In the boundary theory, they can be regarded as the supercooled normal phase and the superconducting phase, respectively. We consider perturbations on supercooled Reissner-Nordström-AdS black holes and study their non-linear time evolution to know about… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
110
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(126 citation statements)
references
References 80 publications
9
110
0
7
Order By: Relevance
“…To answer these questions, we cannot just look at the dual operator on the AdS boundary in an equilibrium system, we need to concentrate on the non-equilibrium dynamics in the bulk gravitational configurations to disclose the process of addressing the scalar hair onto the bald AdS black hole. In [34], the non-equilibrium process in the bulk Einstein-Maxwell-scalar background has been studied. It was observed that during the time evolution, the initial scalar perturbation in the bulk spacetime first moves towards the AdS boundary, it is then bounced back by the AdS wall, grows and moves towards the bald black hole.…”
Section: Jhep02(2016)116mentioning
confidence: 99%
See 4 more Smart Citations
“…To answer these questions, we cannot just look at the dual operator on the AdS boundary in an equilibrium system, we need to concentrate on the non-equilibrium dynamics in the bulk gravitational configurations to disclose the process of addressing the scalar hair onto the bald AdS black hole. In [34], the non-equilibrium process in the bulk Einstein-Maxwell-scalar background has been studied. It was observed that during the time evolution, the initial scalar perturbation in the bulk spacetime first moves towards the AdS boundary, it is then bounced back by the AdS wall, grows and moves towards the bald black hole.…”
Section: Jhep02(2016)116mentioning
confidence: 99%
“…Subsequently this perturbation falls onto the bald hole and accumulates there and finally makes the bald black hole become hairy. The time evolutions of the event and apparent horizons of the bulk black hole in the AdS bulk were disclosed in [34]. Employing the AdS/CFT duality, the authors related the observed properties in the AdS bulk to the boundary CFT, and further they displayed the time dependence of the superconducting order parameter in the holographic superconductor.…”
Section: Jhep02(2016)116mentioning
confidence: 99%
See 3 more Smart Citations